2015
DOI: 10.3906/bot-1504-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bacterial leaf blight resistance genes in wild rice of eastern India

Abstract: An experiment was conducted during the 2013 monsoon season to screen 35 wild rice accessions against the BX043 strain of Xanthomonas oryzae pv. oryzae and identify the presence of bacterial blight resistance genes Xa21, xa13, xa5, Xa4, and Xa2. Among the accessions the area under the disease progress curve ranged from 174.88 (NKSWR-65) to 680.54 (NKSWR-34) compared with resistant controls RP bio-226 (93.92), CRMAS 2231-37 (097.28), CRMAS 2232-71 (098.58), and Tetep (178.62) and susceptible control PB-1 (1065.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
2
14
0
1
Order By: Relevance
“…This might result in occurrence of aggressiveness and high virulence of the Xoo MXO1410 strain. Similarly, a wide range of responses of genotypes to Xoo have been observed and reported (Singh et al, 2015;Fred et al, 2016;Sombunjitt et al, 2017;Acharya et al, 2018). Plants are subjected to a wide range of environmental stresses during their growth and development stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might result in occurrence of aggressiveness and high virulence of the Xoo MXO1410 strain. Similarly, a wide range of responses of genotypes to Xoo have been observed and reported (Singh et al, 2015;Fred et al, 2016;Sombunjitt et al, 2017;Acharya et al, 2018). Plants are subjected to a wide range of environmental stresses during their growth and development stages.…”
Section: Discussionmentioning
confidence: 99%
“…Result was aligned with Yugander et al (2018) by using 38 of modern cultivated Malaysian varieties. Singh et al (2015) also stated that none of the 25 landraces studied had xa13 genes. According to Lore et al (2011), the resistance gene xa13, was originally identified from a land race BJ1 from the Indian subcontinent, and it is exhibiting a wide spectrum of resistance individually or as combination with other resistance genes against multiple Xoo isolates.…”
Section: Discussionmentioning
confidence: 99%
“…The use of microsatellites in selecting for the Xoo resistance gene xa5 and blast R-genes corresponded with Singh et al [18], who adopted RM13 for selecting xa5 gene. Miah et al [9], Hasan et al [19] and Ashkani et al [4] all used microsatellite markers for selecting the blast resistance genes.…”
Section: Foreground Ssr Markersmentioning
confidence: 91%
“…A total of eight foreground markers were confirmed polymorphic from this study which involved the two parental combinations (Putra-1 Â IRBB60). Other researchers who found the markers to be polymorphic in their own parental combinations included Deshmukh et al [15], Dokku et al [16], Ji et al [17] and Singh et al [18].…”
Section: Foreground Ssr Markersmentioning
confidence: 99%
“…Wild genotypes are rich reservoir for resistance source. Singh et al (2015) identified the BB resistance genes in 35 wild rice accessions of Eastern India and from their studies, the accessions NKSWR-25 harbored 3 resistance genes xa5, Xa4 and All the studied polymorphic SSR markers used in this exploration exhibited PIC value of above 0.5, which indicated the existence of high polymorphism in these markers. Similar studies on high informativeness of the SSR markers were reported by Kumar and Bhagwat (2012) and Lang et al (2014).…”
Section: Discussionmentioning
confidence: 87%